Efforts to Improve The Economy of Communities in The Trade and Services Sector in Beach Destinations - Miska Irani Tarigan; Lusiah Lusiah; Errie Margery; Aulia Kusuma Wardani; Sulistyo Budi Utomo; Mazzlida Mat Deli (International Journal of Economics Development Research (IJEDR), 2023)
Every year, the Bau Nyale festival always has a unique concept that attracts the attention of domestic and foreign tourists. Tourism has become a leading sector of Central Lombok Regency in order to realize social welfare for its entire community. This can be seen from the program launched by the Regional Government to become a major tourist destination, not only for local tourists but also foreign tourists. The purpose of this study is to analyze and describe the Bau Nyale festival as an effort to improve the community's economy in the trade and service sector in Selong Belanak beach destination. The research used the descriptive method with qualitative analysis and data were collected through interviews, observation and documentation. The secondary data were collected from documents and texts related to the research topic, be it books, articles journals, or others. The results of this study show that the contribution of tourist attractions and Bau Nyale festival at Selong Belanak Beach has a natural impact, namely increasing the number of tourist visits and increasing employment opportunities for the community and has an effect on the economic income of the local community. This can lead to new business opportunities and open up job opportunities, the needs of the population are met, control and ownership can be fully held by the community. Village government and regency government must provide support to MSMEs around Selong Belanak Beach by improving facilities to improve the community's economy, further campaign for the cultural tourism by managing various facilities and infrastructure that can facilitate tourists in visiting.